The Literary Ecocritism In The Romantic Period Poem “Nachts” By Joseph von Eichendorff - Kasturi, Rayhan Adhya; Dudy Syafruddin (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
Literary works can be a portrait of phenomena that occur in the surrounding nature, both as appreciation and criticism. This research aims to identify the spirit of the times in the poem "Nachts" written in 1826 by Joseph von Eichendorff during the Romantic literary era. In addition, this research also reveals the conception of nature and criticism of natural conditions given by the author. The research method used is descriptive qualitative with a mimetic approach, in which the poem "Nachts" is analysed as the main data source. The results show that this poem reflects human interaction with nature and contains criticism of environmental damage that is relevant to current conditions. In addition, this poem highlights the characteristics of the Romantic era such as appreciation of natural beauty, tranquillity, and self-reflection.